Pengaruh Pu dan Peu terhadap Niat Menggunakan Aplikasi Travel Digital Oleh Wisatawan Senior di Bandung - Sevi Anggraeni; Rahmat Priyanto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
The study also emphasizes the growing role of technology in enhancing the travel experience for senior citizens. With the rapid digitalization of various industries, including the travel sector, the elderly population is increasingly using mobile applications to plan and book trips. However, older adults often face challenges in adapting to new technologies due to physical, cognitive, or sensory limitations. This study’s results underscore the importance of addressing these barriers in the design of travel applications for seniors. The ease of use and perceived usefulness of these applications are not just about functional features but also about how accessible and user-friendly the design is for older users. In addition to the perceived usefulness and ease of use, it is essential for developers to consider the specific needs and preferences of senior travelers, such as larger fonts, clear navigation, and easy-to-understand instructions. Ensuring that these features are incorporated can greatly enhance the adoption of travel applications among the elderly and improve their overall experience. The findings also suggest that fostering trust and confidence in technology among older users can increase their willingness to engage with digital platforms. Furthermore, future research could explore how other factors, such as social influence or experience with technology, interact with perceived ease of use and perceived usefulness to further explain seniors’ behavioral intentions toward digital travel applications. By addressing these factors, developers can create more inclusive and accessible services that cater to an aging population. As the digital landscape continues to evolve, it is crucial to ensure that seniors are not left behind, and that they can enjoy the same convenience and benefits that digital travel services offer to younger generations.